Investigating the Disparity Between the Expectations and the Experiences of Students in a Graduate Programme at a Graduate School in Trinidad and Tobago - Maharaj, Jaidath (My University, 2015)
This study investigated student attrition through an examination of the disparity between student expectations and perceptions of their experiences in a graduate programme at a graduate school in Trinidad and Tobago. Data were collected from three students through interviews. It was found, overall, that service quality gaps existed since the institution created expectations that were not aligning with students’ perceived experiences within the programme.
Keywords: Student attrition; Case studies; Postgraduate students; Postgraduate study; Educational expectations; Educational experience; Trinidad and Tobago